The management of savagery : how America's national security state fueled the rise of Al Qaeda, ISIS, and Donald Trump - Blumenthal, Max, 1977- (London Verso, 2019)
THE MANAGEMENT OF SAVAGERY excavates the real story behind America's dealings with the world and shows how the extremist forces that now threaten peace across the globe are the inevitable flowering of America's imperial designs of a national security state. Washington's secret funding of the Mujahedin provoked the Russian invasion of Afghanistan in 1979. With guns and money, the United States has ever since sustained the extremists, including Osama Bin Laden, who have become its enemies. The Pentagon's willingness to make alliances abroad have seen the war coming home with inevitable consequences: by funding, training, and arming jihadist elements in Afghanistan, Syria, and Libya since the Cold War and waging wars of regime change and interventions that gave birth to the Islamic State. These failed wars abroad have made the United States more vulnerable at home, to both terrorism as well as native ultra-nationalism. The inevitable conclusion of the Neo Con Imperialism is the rise of the Trump presidency. Trump's dealings in the Middle East are likely only to exacerbate the situation.
Introduction : the unstable state -- The Afghan trap -- At the dawn of the forever war -- Waves flanked by arrogance -- In for the rudest of awakenings -- The counter jihad -- The next dirty war -- Until we meet in Damascus -- Regions of savagery -- Collateral damage, indirect benefits -- Attacking our team -- Pawns in the game -- Extinction of the grayzone.
Includes bibliographical references and index.
PB
Keywords: Trump, Donald, -- 1946-; Qaida (Organization); IS (Organization); Imperialism; National security -- United States; United States -- Foreign relations -- Middle East; Middle East -- Foreign relations -- United States; Middle East -- Politics and government -- 1979-; United States -- Politics and government -- 1989-